MODEL TARIKAN KEBUTUHAN PARKIR PADA RUMAH SAKIT UMUM DAERAH DI KALIMANTAN SELATAN - Rina Aryani (Jurnal Teknologi Berkelanjutan, 2019)
The parking lot at the Regional General Hospital (RSUD) in Hulu Sungai Utara Regency, South Kalimantan has experienced overcapacity. This results in the majority of vehicles parked on the road body, which causes discomfort and insecurity for visitors to the facility and traffic on the road. However, when compared to the three hospitals in the nearest regency, namely the Hulu Sungai Tengah District Hospital, Balangan Regency Hospital, and Tabalong District Hospital with wider parking spaces and more regularly parked vehicles will make people comfortable and safe to visit the hospital. The purpose of this study was to determine the effect of the independent variables reviewed on the needs of two-wheeled and four-wheeled parking at regional public hospitals and to determine the model of parking needs at four regional public hospitals. The data used in this study are secondary data obtained from the hospital and primary data obtained from direct surveys in the field. From the results of the analysis, the independent variables dominantly affecting the need for two-wheeled parking are the number of polyclinic visitors (x3), the number of hospitalized patients (x5) and the number of polyclinic patients (x6) while the four-wheeled parking needs are the number of polyclinic visitors (x3), the number of inpatients (x5) and the number of polyclinic patients (x6). The model of parking demand pulling at Amuntai District Hospital is Y1 = 5,317 + 3,909x3 + 1,586x2 and Y2 = 3,383 + 0,282x6, in Balangan Regional Hospital is Y1 = 35,329 + 1,079x3 and Y2 = 5,683 + 0,351x3, at Barabai Regional Hospital is Y1 = 75,630 + 1.533x6 and Y2 = 27.994 + 0.179x6 and at the Tanjung Regional Hospital is Y1 = 4.269 + 0.761x3 + 7.895x5 + 0.444x2 and Y2 = -0.155 + 0.215x2 + 0.111x3 + 1.086x5.